الاتجاه النقدي في التفسير تفسير ابن عاشور نموذجا - Abdo Khaled, Nashwan (Faculty of Quranic and Sunnah Studies, Universiti Sains Islam Malaysia, 2012)
This paper deals with the criticism approach of [Quran] interpretation in general, in order to give the reader a general scientific view for the most significant criticism aspects addressed by the commentators in their Tafaseer. The researcher aims at giving a brief overview of the deductive criticism approach in interpretation. The reader is to be informed that if Ijtihad and deduction terms are present, and conditions of the interpreter are applicable, then there is ample space to explain the verses of the Quran within the guidelines of the explanatory, though it is important not trespass the Quran overall purpose, in order to widen the range of Quran’s semantic, and employing the purposes of the Quran in Tafseer, to the realization of the purposes Quranic interpretation to fit this with the reality of society and the conditions of the times, and that the door of meditation [in the holy Quran] is open, and the infallibility of the Quran is fixed, As for the explanatory opinions they are only different interpretations, and visions that may vary from interpreter to another. The researcher has followed the inductive approach to collect the texts and statements, evidence, and analytical approach to the study of those texts and statements, evidence, and to highlight aspects of the criticism made by some commentators of the other commentators, indicating the depth of Ibn Ashur methodology in his Tafseer book tilted Attanweer Wa Ttahreer. The researcher has concluded this research with a conclusion stating his most important findings.